2005
DOI: 10.1167/iovs.04-0610
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraocular Pressure Measurements in New Zealand White Rabbits

Abstract: All tonometers underestimate IOP, with increasing inaccuracy at higher pressures. The Perkins applanation tonometer was the most reliable for measuring IOP in the range of 0 to 50 mm Hg in New Zealand White rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 13 publications
(12 reference statements)
6
41
0
6
Order By: Relevance
“…With regard to the accuracy, there was a strong correlation between the IOP values obtained with ocular manometry and the IOP values obtained with the Tono-Pen XL ® and Perkins ® tonometers ( Figure 2); however, the Perkins ® tonometer was more accurate than the Tono-Pen XL ® tonometer, producing measurements that were much closer to the real IOP values measured with manometry (Table 1). The Tono-Pen ® XL tonometer underestimated IOPs between 15 and 50mmHg in horses and cattle, which was in agreement with other studies (PRIES et al, 1990;ANDRADA MÁRQUES et al, 2003;PASSAGLIA et al, 2004;LIM et al, 2005;KALESNYKAS & UUSITALO, 2007). Some studies comparing the Tono-Pen XL ® tonometer with other tonometers, such as the Perkins ® and TonoVet ® tonometers in rabbits (KALESNYKAS & UUSITALO, 2007) and the Goldmann tonometer in humans (FRENKEL et al, 1988;IESTER et al, 2001) …”
Section: Discussionsupporting
confidence: 91%
“…With regard to the accuracy, there was a strong correlation between the IOP values obtained with ocular manometry and the IOP values obtained with the Tono-Pen XL ® and Perkins ® tonometers ( Figure 2); however, the Perkins ® tonometer was more accurate than the Tono-Pen XL ® tonometer, producing measurements that were much closer to the real IOP values measured with manometry (Table 1). The Tono-Pen ® XL tonometer underestimated IOPs between 15 and 50mmHg in horses and cattle, which was in agreement with other studies (PRIES et al, 1990;ANDRADA MÁRQUES et al, 2003;PASSAGLIA et al, 2004;LIM et al, 2005;KALESNYKAS & UUSITALO, 2007). Some studies comparing the Tono-Pen XL ® tonometer with other tonometers, such as the Perkins ® and TonoVet ® tonometers in rabbits (KALESNYKAS & UUSITALO, 2007) and the Goldmann tonometer in humans (FRENKEL et al, 1988;IESTER et al, 2001) …”
Section: Discussionsupporting
confidence: 91%
“…A possible animal model for these experiments appears to be the New Zealand white albino rabbit (NZWAR). This is an established model for the investigation of corneal disease (Nakamura et al 2003, Tungsiripat et al 2003, Ivarsen et al 2004, Mimura et al 2005 and AH dynamics (Tsukahara et al 1986, Green et al 1989, Munden & Schmidt 1992, Lim et al 2005. The corticosteroid hormone profile is similar to humans (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…All tonometric measurements were performed by the same ophthalmic surgeon. To correct tonometry estimates that provide a closer approximation of the actual IOP in rabbits; Equation 1 was used as derived by Lim et al 19 from a linear regression study in which they demonstrated that the Tonopen TM XL showed the least error in estimation of true pressure. However, there was a high degree of variability in the measurements, especially at higher IOPs, where it significantly undervalued the IOP.…”
Section: Postoperative Monitoring Of the Rabbitsmentioning
confidence: 99%